The Effect Of Workplace Spirituality on Organizational Climate and Work Culture in Islamic Higher Education - Fitri, Agus Zaenul; Prabowo, Sugeng Listyo (JURNAL AL-TANZIM, 2023)
This article examines the new dimension of workplace spirituality and its influence on the organizational climate and employee work productivity at State Islamic Religious Universities (PTKI). This research used an exploratory mixed methods design. The investigation began with qualitative data collection through in-depth interview techniques, participant observation, and document study, then continued with quantitative research through survey techniques with a sample of 372 people as respondents from 17 IHEs spread throughout Indonesia. Data analysis uses correlation analysis, regression, and path analysis. The findings suggest that a new dimension discovered in workplace spirituality is devotion. The research results show that the higher the workplace spirituality, the higher the organizational climate and employee productivity. Work productivity strengthens the influence of workplace spirituality on organizational climate. This provides empirical evidence that high employee productivity and workplace spirituality will influence and impact the corporate environment. By improving the quality of workplace spirituality, the organizational climate becomes conducive, thereby increasing employee work productivity.